Profiles in neglect of older adult care workers in a long-term care facility: a latent profile analysis - Yan, Chang; Wang, Caili; Ding, Xinshu; Sun, Lefei; Gao, Wei; Liu, Deshan (Frontiers in Public Health, 2024)
Background Neglect is a common form of abuse, and long-term care facilities record higher incidences of this abuse. Given that older adult care workers are the main workforce in these facilities, their neglectful behavior requires public health attention. Internal individual characteristics can lead to older adult abuse, and managing workers who abuse older adults may require various methods. This study aimed to identify the profiles of neglect among older adult care workers in long-term care facilities and explore the influencing factors of neglect. Methods In this cross-sectional study, a convenience sample of older adult care workers from 15 long-term care facilities in Shandong Province (N = 421) completed a questionnaire on the characteristics associated with neglect. Latent profile analysis was used to identify distinct neglect profiles and promote the understanding of individual characteristics associated with varying levels of neglect. One-way analysis of variance and multivariate logistic regression analyses were used to examine the population characteristic differences. Results Older adult care workers exhibited three neglect profiles, namely, the “low-risk group,” “medium-risk group,” and “high-risk group.” Males, participants with no employment qualification certificate, and those who did not attend regular training represented the majority of those in the “high-risk group.” Participants with a monthly income of more than ¥ 4,000 and nursing 1–2 older adults simultaneously represented the majority of those in the “low-risk group.” Conclusion Long-term care facility administrators should tailor interventions to individual care worker profiles to reduce neglect behaviors and improve care levels.